Institutional Analysis of Watershed Manangement in Batam Island - Syahrul Donie (Universitas Muhammadiyah Surakarta, 2016)
This study aimed to look at the institutional condition of the current watershed management and institutional models (management authority) which were relevant to Batam Island in the future. The data collection was conducted by interview techniques and was validated through focus group discussions. The data were described and analyzed with SCP (structure, conduct, performance) method for relevant stakeholders’ data, legislation, and with KIPA (quadrant interpretative performance analysis) method for data of interest and power of stakeholders. The results showed that the watershed management institutional in Batam Island was still overlapping. According to the regulations, the Management Board (BP) of Batam Island was given the authority to manage and to use land and water; on the other hand the Local Government (Mayor) was facilitated by BPDAS KEPRI (Watershed Management Institute of Riau Islands) to also arrange an integrated watershed management. The results of discussions showed that BP Batam was an institute of having interest and power as well as key position in achieving successful watershed management. Based on this study, it was suggested that BP Batam should be given authority in watershed management in Batam Island, which keeps referring to the norms, standards, procedures, and indicators set by the central government.